Multiprofessional and Cross-Sectoral Co-operation in the Promotion of Health and Wellbeing of Children, Adolescents, and their Families - Kitinoja, Helli; Nissinen, Kaija; Kasanen, Maria; Salminen-Tuomaala, Mari (European Journal of Applied Sciences, 2024)
Aims: The objective of this study was to describe experiences about multiprofessional and cross-sectoral co-operation, its forms, success, and challenges, in promoting the overall health and wellbeing of children, adolescents and their families in the Healthy Kids of Seinäjoki (HKS) action model. Methods: The European Commission Criteria to select best practices in health promotion and chronic disease prevention and management in Europe (2017) was used as a theoretical framework in the current state analysis of the HKS action [1]. Several methods were used in collecting the data: policy documents of the City of Seinäjoki, electronic survey to all the staff members, interviews of the directors and virtual workshops for the key informants. Data collected by the electronic survey was analysed by using the SPSS statistical programme and other data collected by using inductive content analysing. Results: In the policy documents and in directors´ interviews all city sectors were seen as actors in the promotion of health and wellbeing of children, adolescents, and their families, in the survey 68% of the respondents experienced that they co-operate a lot or to some extent with the other sectors. Co-operation with the actors outside city sectors was seen weak. Multiprofessional teamwork, transfer meetings and integrated services were seen as best practices. Challenges were seen to be development of co-operation and information sharing. Conclusions: Coordination of services, multiprofessional teamwork, cross-sectoral comprehensive working methods and holistic thinking are needed to develop in the promotion of health and wellbeing of children, adolescents, and their families.